2014
DOI: 10.1039/c3nj01401k
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis of pyrochlore-type cubic tungsten trioxide hemihydrate and high photocatalytic activity

Abstract: Pyrochlore-type cubic phase tungsten trioxide hemihydrate (c-WO 3 Á0.5H 2 O) has been synthesized for the first time via a simple solvothermal process. The photocatalytic properties have been investigated firstly by the photodegradation of RhB, where the c-WO 3 Á0.5H 2 O sample demonstrated high photocatalytic activity, indicating that c-WO 3 Á0.5H 2 O is a promising candidate for tungsten oxide-based photocatalytic materials. The investigation result of the crystal water effects on the photocatalytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In order to study the effect of crystal water of as-prepared tungsten oxides on their photodegradation and water oxidaton properties, dehydration through annealing treatment at 473 K for 10 h is carried out for h-WO 3 ·0.33H 2 O, c-WO 3 ·0.5H 2 O and h/c-WO 3 ·nH 2 O photocatalysts, which is based on the work of Chen and co-workers [43]. The XRD patterns of the three dehydrated samples (as shown in Figure S3) exhibit the peaks shift to a higher 2Â value due to the smaller lattice spacing after the loss of crystal water.…”
Section: Mechanism's Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the effect of crystal water of as-prepared tungsten oxides on their photodegradation and water oxidaton properties, dehydration through annealing treatment at 473 K for 10 h is carried out for h-WO 3 ·0.33H 2 O, c-WO 3 ·0.5H 2 O and h/c-WO 3 ·nH 2 O photocatalysts, which is based on the work of Chen and co-workers [43]. The XRD patterns of the three dehydrated samples (as shown in Figure S3) exhibit the peaks shift to a higher 2Â value due to the smaller lattice spacing after the loss of crystal water.…”
Section: Mechanism's Discussionmentioning
confidence: 99%
“…It is well known that RhB is a colored dye which mainly absorbs visible light of wavelength 552 nm, and the as-prepared h/c-WO 3 ·H 2 O can only absorb light of wavelength shorter than 430 nm. Therefore, the degradation process may be driven by the photosensitization of RhB under visible light irradiation ( > 420 nm) [42,43]. In order to avoid the photosensitization effect of RhB, we further explored water oxidation experiments using different irradiation conditions to clarify the intrinsic photocatalysis of h/c-WO 3 ·nH 2 O homojunction.…”
Section: Material's Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although wet chemistry methods can well control the structure of obtained W-based materials, they require prolonged reaction times and highly controlled reaction conditions including temperature, pH value and raw materials ratio [27,28]. In addition, it needs an enormous amount of time to wash the obtained sample and the resulting acid/basic solutions are unfriendly to environment.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [34] prepared hierarchical WO 3 Á H 2 O hollow microspheres with 94.8% of Rh B (1 Â 10 À 5 M) degradation in 6 h (500 W). Zheng et al [35] synthesized aggregated nanoparticles of cubic WO 3 Á 0 Á 5H 2 O which could degrade 70% of Rh B (10 mg/L) within 200 min under visible light (300 W). Li et al [36] reported orthorhombic WO 3 visible light (300 W) for 100 min.…”
Section: Introductionmentioning
confidence: 99%